How Reliable is the Surgeon's Ability to Differentiate between Idiopathic and Degenerative Deformity in Adults; What Parameters Help them Decide?. Issue 1 (April 2016) - Acaroglu, Emre; Güler, Ümit Özgür; Ayhan, Selim; Mmopelwa, Tiro; Sabat, Montse Domingo; Pellise, Ferran; Perez-Grueso, Francisco Javier Sanchez; Alanay, Ahmet; Obeid, Ibrahim; Kleinstuck, Frank
Introduction: Adult spinal deformity (ASD) may be classified as idiopathic (I) or degenerative (D) (or other) based on classifier's perception, the reliability of and factors inherent to which remain unknown. Aim of study is to evaluate the inter and intraobserver reliability of surgeons' perception in differentiating I from D ASD and to identify the determinants of it. Material and Methods: From a multicentric prospective database, 179 patients were identified with the diagnosis of I ( n  = 103) or D ( n  = 76); no previous surgery; and a lumbar coronal curve > 20°. Standing AP and lateral X-Rays were sent to five experienced spine surgeons to be identified as D or I (or other); followed by a second round after reshuffling. Weighted Kappa statistics was used, after which the patients were stratified by number of agreements as perfect (10/10) and very good (≥8/10); these were further compared for additional radiological parameters. Results: Four observers completed both rounds while the 5th did only the first (a total of 10 observations/pt including the record). Agreement levels were moderate to good for intra but fair to moderate for interobserver comparisons (Table 1). There were 42 perfect and 80 with very good agreements for I patients but only 6 perfect and 17 very good agreements for D. Upon comparison of these, it was seen that they were different for some coronal parameters such as lumbar Cobb angle (larger in I, p  < 0.001), CSVL modifier (C more common in I, p  = 0.007) and presence of rotatory subluxation (less common in D, p  = 0.017) but very different for sagittal parameters (lumbar lordosis, sagittal vertical axis, T2-sagittal tilt, pelvic tilt, sacral slope and global tilt; increased sagittal imbalance in D, all p≤0.001). Conclusion: Surgeons in this study demonstrated reasonable intraobserver agreement but only fair agreement amongst them. These findings suggest that especially in patients with significant coronal curves, determination of curve etiology with only radiological data may not be accurate. In patients with good agreement, the most consistent radiologic determinant appeared to be the presence of sagittal imbalance.